Regulation of Ferroptosis Pathway by Ubiquitination - Wang, Xinbo; Wang, Yanjin; Li, Zan; Qin, Jieling; Wang, Ping (Frontiers in Cell and Developmental Biology, 2021)
Ferroptosis is an iron-dependent form of programmed cell death, which plays crucial roles in tumorigenesis, ischemia-reperfusion injury and various human degenerative diseases. Ferroptosis is characterized by aberrant iron- and lipid-metabolisms. Mechanistically, excess of catalytic iron is capable of triggering lipid peroxidation followed by Fenton reaction to induce ferroptosis. The induction of ferroptosis can be inhibited by sufficient glutathione (GSH) synthesis via system Xc- transporter-mediated cystine-uptake. Therefore, induction of ferroptosis by inhibition of cystine-uptake or dampening of GSH synthesis has been considered as novel strategy for cancer therapy. While reversal of ferroptotic effect is able to delay progression of diverse disorders, such as cardiopathy, steatohepatitis and acute kidney injury. The ubiquitin (Ub)–proteasome pathway (UPP) dominates the majority of intracellular proteins degradation by coupling Ub molecules to the lysine residues of protein substrate which is subsequently recognized by the 26S proteasome for degradation. Ubiquitination is crucially involved in a variety of physiological and pathological processes. Modulation of ubiquitination system has been exhibited to be potential strategy for cancer treatment. Currently, more and more emerged evidence has demonstrated that ubiquitous modification is involved in ferroptosis and dominates the vulnerability to ferroptosis in multiple types of cancer. In this review, we will summarize current findings of ferroptosis surrounding the viewpoint of ubiquitination regulation. Furthermore, we also highlight the potential effect of ubiquitination modulation on the perspective of ferroptosis-targeted cancer therapy.